6a-3=1-2a

Simple and best practice solution for 6a-3=1-2a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a-3=1-2a equation:



6a-3=1-2a
We move all terms to the left:
6a-3-(1-2a)=0
We add all the numbers together, and all the variables
6a-(-2a+1)-3=0
We get rid of parentheses
6a+2a-1-3=0
We add all the numbers together, and all the variables
8a-4=0
We move all terms containing a to the left, all other terms to the right
8a=4
a=4/8
a=1/2

You can always share this solution

See similar equations:

| y–4+1=18 | | 5^x-4=275 | | 4.26-2n=17.04 | | 5^x4=275 | | 7t-11=2t | | h+19=39 | | 12.3+v=22.32 | | 2x1=x4 | | r-38=3 | | 48-d=34 | | 31/3+2a=5a+1/3 | | 50-a/11=58 | | 2w+2(w+w)=24 | | 5x^{2}-2x=0` | | 2^3x.2^2x=64 | | `5x^{2}-2x=0` | | –6(–3+2z)= | | x+(1/2)x=13500 | | x–21=9 | | n/12=15/36+n | | 9+6/7b=68 | | 2(4k+3-13=2(18-k)-13 | | x^2+2x+6x+12=x+6 | | 3x=4x+47 | | 0=2x2-23x-39 | | (3x-2)+2x+5)=180 | | 35=x-46 | | 4x+47=3 | | 15+2x-1x=60 | | -4(3x+7)=-172 | | 3.1x=55.8 | | y-26=30 |

Equations solver categories